Preparation method of bifunctional multiphase noble metal catalyst and application of bifunctional multiphase noble metal catalyst in low-temperature rapid hydrogen release of slurry hydrogen storage and production material
By modifying zeolite-loaded precious metals to prepare dual-function catalysts, the problems of oxidation film obstacles during the hydrolysis of aluminum-based materials and the slow hydrogen release rate of organic liquid hydrogen storage materials are solved, and efficient hydrolysis hydrogen production and hydrogen release efficiency is achieved, simplifying the design of hydrogen production system and reducing costs.
Patent Information
- Application Number
- CN202510104814.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-01-23
AI Technical Summary
During the hydrolysis process, the surface of aluminum-based materials is prone to form oxide films, hindering reactions; the hydrogen release rate of organic liquid hydrogen storage materials is slow, and heat production cannot be absorbed in time; the material and heat transfer problems between different phases affect the overall reaction rate.
Bifunctional multiphase precious metal catalysts are prepared by using amphiphilic organic molecular modified zeolite as a support and supporting precious metals. The modified zeolite is prepared by liquid-phase electrochemical plating and impregnation treatment, combined with reduction treatment, and a catalyst with catalytic aluminum hydrolysis and hydrogen release functions of organic liquid hydrogen storage materials.
It significantly improves the efficiency of hydrogen production by hydrolysis of aluminum-based materials and hydrogen release by organic liquid hydrogen storage materials, solves the problems of oxidation film obstacles and heat transfer, simplifies the design of hydrogen production system, and reduces costs.
Smart Images

Figure CN119857537A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of hydrogen production materials, and specifically relates to a method for preparing a bifunctional multiphase precious metal catalyst, and also relates to the application of the bifunctional multiphase precious metal catalyst in the low-temperature rapid release of hydrogen from slurry hydrogen storage and production materials. Background Art
[0002] Hydrogen energy has the advantages of high calorific value, recyclability and environmental protection. It is one of the most promising new energy sources. However, how to achieve efficient storage and preparation of hydrogen has become an important bottleneck restricting the large-scale development of hydrogen energy.
[0003] Patent CN118598073A discloses an aluminum-based slurry hydrogen storage material and its preparation method. The method uses organic liquid hydrogen storage material to coat nano-microcrystalline aluminum-based powder. The aluminum-based slurry hydrogen storage material has the advantages of controllable reaction process and stable hydrogen production rate. It effectively solves the problem of poor continuity of hydrogen production of traditional aluminum-based materials. It is a hydrogen production technology with great development prospects. However, this technology faces the following problems in practical application: First, a dense oxide film is easily formed on the surface of aluminum during the hydrolysis process, which hinders the further occurrence of aluminum hydrolysis reaction; second, the hydrogen release rate of organic liquid hydrogen storage material is slow, and the heat generation cannot be consumed in time, which limits the hydrogen production; third, the hydrolysis hydrogen production reaction of aluminum-based slurry hydrogen storage material faces the problem of material and heat transfer between different phases, which has a significant impact on the rate of the overall hydrolysis hydrogen production reaction.
[0004] In order to solve the problem of oxide film on the surface of aluminum-based materials, patent CN116022733B proposes to combine aluminum with zeolite materials and effectively remove the oxide film on the aluminum surface by using the unique internal porous skeleton structure of zeolite. However, zeolite has almost no catalytic effect on organic liquid hydrogen storage materials, and directly combining it with the hydrogen release catalyst of traditional organic liquid hydrogen storage materials will increase the complexity and cost of the hydrogen production system.
[0005] Based on this, developing catalysts with excellent performance to synergistically improve the efficiency of hydrogen production and release by hydrolysis is an issue that urgently needs to be addressed in the current technical field. Summary of the invention
[0006] One of the purposes of the present invention is to provide a method for preparing a bifunctional multiphase precious metal catalyst that can synergistically improve the amount of hydrogen produced and the hydrogen release efficiency of organic liquid hydrogen storage materials by hydrolysis, and promote the low-temperature rapid hydrogen release of organic liquid hydrogen storage materials.
[0007] A second object of the present invention is to provide a bifunctional multiphase precious metal catalyst for use in low-temperature rapid hydrogen release of slurry hydrogen storage and production materials.
[0008] The technical solution adopted by the present invention to achieve one of the objectives is: to provide a method for preparing a bifunctional multiphase precious metal catalyst, comprising the following steps: The modifier is dissolved in a solvent to obtain a modifier solution; the modifier is selected from amphiphilic organic molecules having hydrophilic and lipophilic groups or structures; zeolite is added to the modifier solution and liquid phase chemical plating is performed to obtain a modified zeolite; the modified zeolite is placed in a noble metal salt solution for immersion treatment, and then placed in a reducing atmosphere for reduction treatment to obtain a bifunctional multiphase noble metal catalyst.
[0009] The overall idea and inventive principle of the present invention are as follows: The present invention uses amphiphilic organic molecules with hydrophilic and lipophilic groups or structures to modify zeolite to prepare a modified zeolite. Zeolite is an ideal choice for catalyst carriers due to its unique porous skeleton structure. Combining the commonly used active components of hydrogen release catalysts of organic liquid hydrogen storage materials, such as palladium (Pd), platinum (Pt), iridium (Ir) and other precious metals with the modified zeolite material can provide a dual-function catalyst for aluminum-based slurry hydrogen storage and production materials that catalyzes aluminum hydrolysis to produce hydrogen and catalyzes the release of hydrogen from organic liquid hydrogen storage materials. The internal porous skeleton structure of zeolite can effectively remove the oxide film on the surface of aluminum, thereby promoting the process of aluminum hydrolysis to produce hydrogen. This process is an exothermic reaction, and the heat released can provide thermal energy for the noble metal-catalyzed organic liquid hydrogen storage material to release hydrogen, further improving the hydrogen release efficiency. Zeolite modified with amphiphilic organic molecules exhibits excellent adsorption properties for both aqueous and organic phases, which is conducive to the rapid transfer of heat from the aqueous phase to the organic phase, effectively solving the problem of heat transfer between the organic liquid hydrogen storage material and water due to the immiscibility of the two, and achieving efficient thermal coupling.
[0010] Furthermore, the modifier is selected from a combination of one or more of octadecylamine ODA, trimethylchlorosilane TMS, and n-octadecyltrichlorosilane OTS. Organic molecules such as ODA, TMS, and OTS are adsorbed on the acidic sites on the surface of the zeolite, and this adsorption mainly occurs in the form of a chemical reaction, which ensures its stability on the surface of the zeolite. Since these molecules carry lipophilic alkyl chains and hydrophilic amine groups, the modified zeolite obtained has a strong adsorption capacity for both the aqueous phase and the organic phase, greatly improving the hydrogen release rate of the catalyst-catalyzed aluminum hydrolysis and the organic liquid hydrogen storage material, which is conducive to the rapid transfer of heat from the aqueous phase to the organic phase, and realizes efficient thermal coupling.
[0011] Furthermore, the solvent includes one of ethanol, toluene, methanol and ethylbenzene.
[0012] Furthermore, the concentration of the modifier solution is 0.01-0.2 g / mL, and the mass volume ratio of zeolite to the modified solution is 0.1-0.5 g / mL. Preferably, the mass ratio of the modifier to the zeolite is (1-10):20.
[0013] Furthermore, the zeolite includes one or more combinations of Hγ zeolite, TS-1 zeolite, HZSM-5 zeolite, MCM-22 zeolite, and mordenite.
[0014] Furthermore, the liquid phase chemical plating is carried out under stirring conditions, the stirring temperature is 20-50° C., and the stirring time is 2-4 hours.
[0015] Furthermore, the noble metal of the noble metal salt solution includes one or more of Pd, Pt, and Ir; the loading amount of the noble metal in the bifunctional heterogeneous noble metal catalyst is 0.5wt.%-3wt.%, preferably 1wt.%. The modified zeolite is immersed in the noble metal salt solution for 3-5h.
[0016] Furthermore, the temperature of the reduction treatment is 350-550°C, and the time is 3-5h. Preferably, the reduction atmosphere is a mixed gas composed of hydrogen and argon in a volume ratio of 1:(5-20); the heating rate of the reduction treatment is 4-6°C / min.
[0017] The technical solution adopted by the present invention to achieve the second purpose is: to provide a bifunctional multiphase precious metal catalyst prepared by the preparation method described in one of the purposes of the present invention for use in the low-temperature rapid release of hydrogen from a slurry hydrogen storage material. Under an inert atmosphere, the bifunctional multiphase precious metal catalyst is mixed with aluminum powder and subjected to ball milling to obtain an activated aluminum hydrolysis hydrogen production material; the activated aluminum hydrolysis hydrogen production material is then mixed with an organic liquid hydrogen storage material and subjected to ball milling to obtain an aluminum-based slurry hydrogen storage material.
[0018] Furthermore, the mass ratio of the bifunctional multiphase precious metal catalyst to aluminum powder is 1:4, the rotation speed of the ball milling treatment is 300-500r / min, and the time of the ball milling treatment is 1-3h; the mass ratio of the activated aluminum hydrolysis hydrogen production material to the organic liquid hydrogen storage material is 1:(3-5).
[0019] Furthermore, the organic liquid hydrogen storage material includes a combination of one or more of fully hydrogenated N-propylcarbazole (12H-NPCZ), fully hydrogenated dibenzyltoluene (18H-DBT), fully hydrogenated 2-methylindole (8H-2-MID), and fully hydrogenated N-ethylcarbazole (12H-NECZ).
[0020] Furthermore, different types of precious metals are selected to prepare bifunctional catalysts for different organic liquid hydrogen storage materials to achieve better catalytic effects. Studies have found that precious metals Pd and Ir have good catalytic effects on the release of hydrogen from 12H-NPCZ and 8H-2-MID, and Pt has a good catalytic effect on the release of hydrogen from 18H-DBT.
[0021] Furthermore, in the aluminum-based slurry hydrogen storage material, the organic liquid hydrogen storage material, under the action of the activated aluminum hydrolysis hydrogen production material, has a hydrogen release conversion rate of 77.2%-87.8% when hydrolyzed for 20 minutes at an ambient temperature of 70-100°C.
[0022] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention provides a method for preparing a bifunctional multiphase precious metal catalyst, using an amphiphilic organic molecule having a hydrophilic and lipophilic group or structure as a modifier to modify zeolite to obtain a modified zeolite. The modified zeolite is then used as a carrier to load precious metals to prepare a bifunctional multiphase precious metal catalyst. The amphiphilic organic molecules grafted onto the surface of the zeolite can enhance the adsorption capacity of the zeolite for the organic phase and the aqueous phase, and the loaded precious metal active components (such as Pd, Pt, Ir, etc.) enable the zeolite to simultaneously have a bifunctional catalytic effect of promoting aluminum hydrolysis to produce hydrogen and increasing the hydrogen release rate of the organic liquid, thereby significantly improving the overall efficiency of the hydrogen production system.
[0023] (2) The bifunctional multiphase noble metal catalyst provided by the present invention uses modified zeolite as a carrier to load the noble metal active component. This catalyst is compounded with aluminum in subsequent applications, which not only effectively solves the obstruction problem of the surface oxide film of aluminum during hydrolysis, but also realizes efficient heat and material transfer between water and organic liquid hydrogen storage materials. The present invention simplifies the design of the hydrogen production system, reduces costs, and provides reliable technical support for the large-scale application of aluminum-based slurry hydrogen storage and production materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The figure is a comparison chart of the change of the amount of hydrogen produced by hydrolysis over time in the application of the catalysts prepared in various embodiments of the present invention and the comparative examples. DETAILED DESCRIPTION
[0025] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0026] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.
[0027] The present invention provides a method for preparing a bifunctional heterogeneous noble metal catalyst, comprising the following steps: Step 1: dissolving a modifier in a solvent to obtain a modifier solution; the modifier is selected from a combination of one or more of octadecylamine (ODA), trimethylchlorosilane (TMS), and n-octadecyltrichlorosilane (OTS); the solvent is selected from ethanol or toluene; the concentration of the modifier solution is 0.01-0.2 g / mL.
[0028] Step 2: Add zeolite to the modifier solution and perform liquid phase chemical plating to obtain modified zeolite; the zeolite includes one or more of Hγ zeolite, TS-1 zeolite, HZSM-5 zeolite, MCM-22 zeolite, and mordenite. The mass volume ratio of zeolite to the modified solution is 0.1-0.5 g / mL; the mass ratio of the modifier to the zeolite is (1-10):20; the liquid phase chemical plating is performed under stirring conditions, the stirring temperature is 20-50°C, and the stirring time is 2-4 hours.
[0029] The modified zeolite is then placed in a noble metal salt solution for immersion treatment, and then placed in a reducing atmosphere for reduction treatment to obtain a bifunctional multiphase noble metal catalyst. The noble metals in the noble metal salt solution include a combination of one or more of Pd, Pt, and Ir; the loading amount of the noble metal in the bifunctional multiphase noble metal catalyst is 1wt.%; the time for the modified zeolite to be immersed in the noble metal salt solution is 3-5h. The temperature of the reduction treatment is 350-550℃, and the time is 3-5h; the reducing atmosphere is a mixed gas composed of hydrogen and argon in a volume ratio of 1:(5-20); the heating rate of the reduction treatment is 4-6℃ / min.
[0030] The present invention will be further described below in conjunction with specific embodiments, but the present invention is not limited thereto.
[0031] Example 1 This embodiment provides a method for preparing a bifunctional multiphase Pd-based catalyst for low-temperature rapid hydrogen release of a slurry hydrogen storage and production material, comprising the following steps: Step 1: Add 0.5 g of octadecylamine (ODA) to 50 ml of ethanol to prepare a solution. Add 10 g of Hγ zeolite to the above ODA solution in a constant temperature water bath at 30°C and stir for 12 hours to achieve liquid phase chemical plating of zeolite. Subsequently, the modified zeolite sample is fully dried to obtain ODA-Hγ zeolite.
[0032] Step 2: Weigh 0.1065 g of palladium acetate and add 15 ml of acetone to prepare a solution. Add 4.95 g of the above ODA-Hγ zeolite to the solution and soak for 4 h. After drying, place the sample in 10% H 2 / Ar atmosphere and then heated to 450°C at 5°C / min for 4h to obtain Pd / ODA-Hγ catalyst.
[0033] Comparative Example 1 The difference between this comparative example and Example 1 is that a Hγ zeolite sample that has not been treated with ODA is used as a carrier, and the obtained catalyst is recorded as Pd / Hγ catalyst.
[0034] Example 2 This embodiment provides a method for preparing a bifunctional multiphase Pt-based catalyst for low-temperature rapid hydrogen release of a slurry hydrogen storage and production material, the method comprising the following steps: Step 1: Add 5 g of TMS to 20 g of toluene to prepare a solution. Weigh 10 g of TS-1 zeolite and add it to the above solution. Stir magnetically at room temperature for 2 h, filter and wash the precipitate with toluene, and dry the precipitate at 100 °C to obtain TMS-TS-1 zeolite.
[0035] Step 2: Weigh 0.1053 g H 2 PtCl 6 4.95 g of the above TMS-TS-1 zeolite was added to the solution and fully immersed for 4 h. After drying, the sample was placed in 10% H 2 / Ar atmosphere and then heated to 450°C at 5°C / min for 4h to obtain Pt / TMS-TS-1 catalyst.
[0036] Comparative Example 2 The difference between this comparative example and Example 2 is that a TS-1 zeolite sample that has not been treated with TMS is used as a carrier, and the obtained catalyst is recorded as Pt / TS-1 catalyst.
[0037] Example 3 This embodiment provides a method for preparing a bifunctional multiphase Ir-based catalyst for low-temperature rapid hydrogen release of a slurry hydrogen storage and production material, the method comprising the following steps: Step 1: Weigh 10 g of TS-1 zeolite, add 5 mL of deionized water and stir evenly, then add 100 mL of toluene solution containing 5 mmol of n-octadecyltrichlorosilane (OTS), stir well, filter and purify with CCl 4 The precipitate was washed with ethanol and dried to obtain OTS-TS-1 zeolite.
[0038] Step 2: Weigh 0.1313 g H 2 IrCl 6 6H 2 O and 15 ml of aqueous solution were prepared into a solution. 4.95 g of the above OTS-TS-1 zeolite was added to the solution and fully immersed for 4 h. After drying, the sample was placed in 10% H 2 / Ar atmosphere and then heated to 450 °C at 5 °C / min for 4 h to obtain Ir / OTS-TS-1 catalyst.
[0039] Comparative Example 3 The difference between this comparative example and Example 3 is that a TS-1 zeolite sample that has not been treated with OTS is used as a carrier, and the obtained catalyst is recorded as Ir / TS-1 catalyst.
[0040] Comparative Example 4 The difference between this comparative example and Example 1 is that Acid-Hγ zeolite is used as a carrier, and the obtained catalyst is recorded as Pd / Acid-Hγ catalyst. The preparation method of Acid-Hγ zeolite is as follows: 10g Hγ zeolite is taken, 100mL 3mol / L HNO 3 The solution was fully stirred at 60°C for 24 h and washed with deionized water to obtain Acid-Hγ zeolite.
[0041] Comparative Example 5 The difference between this comparative example and Example 1 is that Alkali-Hγ zeolite is used as a carrier, and the obtained catalyst is recorded as Pd / Acid-Hγ catalyst. The preparation method of Alkali-Hγ zeolite is as follows: 10g of Hγ zeolite is taken, 100mL of 0.8mol / L NaOH solution is added, and the mixture is stirred at 60°C for 24h, and Alkali-Hγ zeolite is obtained after washing with deionized water.
[0042] Comparative Example 6 The difference between this comparative example and Example 1 is that MCM-22 zeolite is used as a carrier, and the obtained catalyst is recorded as Pd / MCM-22 catalyst.
[0043] Comparative Example 7 The difference between this comparative example and Example 1 is that mordenite is used as a carrier, and the obtained catalyst is recorded as Pd / mordenite catalyst.
[0044] Comparative Example 8 The difference between this comparative example and Example 1 is that multi-walled carbon nanotubes CNT are used as carriers, and the obtained catalyst is recorded as Pd / CNT catalyst.
[0045] Application Examples In an inert gas environment, 2 g of the catalyst prepared in each of the above embodiments and comparative examples was mixed with 8 g of aluminum powder (average particle size 50 μm), and mechanical ball milling was performed (ball-to-material ratio 10:1, ball milling time 2 hours, ball milling speed 400 rpm) to prepare an activated aluminum hydrolysis hydrogen production material; in an inert gas environment, 5 g of the activated aluminum hydrolysis hydrogen production material was mixed with 20 g of an organic liquid hydrogen storage material, and ball milling was performed (ball-to-material ratio 10:1, ball milling time 2 hours, ball milling speed 400 rpm) to obtain an aluminum-based slurry hydrogen storage material.
[0046] According to the different organic liquid hydrogen storage materials used in each embodiment and comparative example, the aluminum-based slurry hydrogen storage material prepared in Example 1 is recorded as Al (Pd / ODA-Hγ) -12H-NPCZ; the aluminum-based slurry hydrogen storage material prepared in Comparative Example 1 is recorded as Al (Pd / Hγ) -12H-NPCZ. The aluminum-based slurry hydrogen storage material prepared in Example 2 is recorded as Al (Pt / TMS-TS-1) -18H-DBT; the aluminum-based slurry hydrogen storage material prepared in Comparative Example 2 is recorded as Al (Pt / TS-1) -18H-DBT. The aluminum-based slurry hydrogen storage material prepared in Example 3 is recorded as Al (Ir / OTS-TS-1) -8H-2-MID. The aluminum-based slurry hydrogen storage material prepared in Comparative Example 3 is recorded as Al (Ir / TS-1) -8H-2-MID. The aluminum-based slurry hydrogen storage materials prepared in Comparative Examples 4-8 were respectively recorded as Al(Pd / Acid-Hγ)-12H-NPCZ, Al(Pd / Alkali-Hγ zeolite)-12H-NPCZ, Al(Pd / MCM-22)-12H-NPCZ, Al(Pd / mordenite)-12H-NPCZ, and Al(Pd / CNT)-12H-NPCZ.
[0047] Application performance testing At 90°C, 5 grams of the aluminum-based slurry hydrogen storage material prepared in the above application example was placed in a two-necked flask, and 50 ml of deionized water was added. The hydrogen produced during the reaction was collected by the drainage gas collection method, and the weight change of the discharged water was monitored in real time to draw a curve of the change in hydrogen production over time. The total hydrogen production volume V after the reaction was completed was calculated, and the liquid phase product in the two-necked flask was allowed to stand for stratification, and the organic phase was analyzed by gas chromatography-mass spectrometry (GC-MS) to determine the hydrogen release volume V of the organic liquid hydrogen storage material. LOHC , and then calculate the volume of hydrogen V produced by the aluminum hydrolysis reaction Al (The above volumes are all converted to the volume under standard conditions). Comparison of the curves of the amount of hydrogen produced by hydrolysis of the catalysts prepared in Examples 1-3 and Comparative Examples 1-8 during application over time Figure 1 As shown, the hydrogen production and conversion rate of each component in Examples 1-3 and Comparative Examples 1-8 after hydrolysis for 80 min are shown in Table 1.
[0048] Depend on Figure 1 It can be seen that under the catalytic action of the catalyst provided in Examples 1-3, high conversion rate hydrogen release of 12H-NPCZ, 8H-2-MID, and 18H-DBT can be achieved under the test conditions of 90°C without the need for a higher temperature. Al(Pd / ODA-Hγ)-12H-NPCZ, Al(Pt / TMS-TS-1)-18H-DBT, and Al(Ir / OTS-TS-1)-8H-2-MID prepared in the application example can achieve conversion rates of 86.3%, 77.2%, and 87.8% in 20 minutes, respectively. Compared with the unmodified catalysts (Comparative Examples 1-3), the hydrogen release conversion rates are significantly improved.
[0049] Table 1
[0050] Furthermore, from Table 1 above, Based on the comparison between Example 1 and Comparative Example 1, Example 2 and Comparative Example 2, and Example 3 and Comparative Example 3, it can be seen that organic molecules such as ODA, TMS, and OTS are adsorbed on the acidic sites on the surface of the zeolite, and this adsorption mainly occurs in the form of chemical reactions, ensuring their stability on the surface of the zeolite. Since these molecules carry lipophilic alkyl chains and hydrophilic amine groups, the modified ODA-Hγ, TMS-TS-1, and OTS-TS-1 zeolites have strong adsorption capacity for both aqueous and organic phases, greatly improving the hydrogen release rate of the catalyst-catalyzed aluminum hydrolysis and the organic liquid hydrogen storage material, which is conducive to the rapid transfer of heat from the aqueous phase to the organic phase, and realizing efficient thermal coupling.
[0051] Based on the comparison between Example 1 and Comparative Example 4, and Example 1 and Comparative Example 7, it can be seen that the acid-treated Hγ zeolite and mordenite have weak adsorption capacity for organic phase, and the performance of catalyzing hydrogen release of organic liquid hydrogen storage materials is poor.
[0052] Based on the comparison between Example 1 and Comparative Example 5, and Example 1 and Comparative Example 6, it can be seen that the alkali-treated Hγ zeolite and MCM-22 have weak adsorption capacity for water phase, which reduces the rate of hydrogen production by aluminum hydrolysis and reduces the heat transfer efficiency, and the hydrogen release performance of the organic liquid hydrogen storage material decreases.
[0053] Based on the comparison between Example 1 and Comparative Example 8, it can be seen that when an inert carrier such as multi-walled carbon nanotubes is used, the formation of surface oxide film during the hydrolysis process of the aluminum-based material cannot be suppressed, the aluminum hydrolysis reaction is hindered, and sufficient heat cannot be generated for the organic liquid hydrogen storage material to release hydrogen.
[0054] The above are only preferred embodiments of the present invention, and are not intended to limit the implementation methods and protection scope of the present invention. Those skilled in the art should be aware that all solutions obtained by equivalent substitutions and obvious changes made using the contents of the specification of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a bifunctional heterogeneous noble metal catalyst, characterized in that: The following steps are involved: dissolving a modifier in a solvent to obtain a modifier solution; the modifier is selected from amphiphilic organic molecules having hydrophilic and lipophilic groups or structures; Adding zeolite into a modifier solution and performing liquid phase chemical plating to obtain modified zeolite; The modified zeolite is placed in a noble metal salt solution for impregnation treatment, and then placed in a reducing atmosphere for reduction treatment to obtain a bifunctional multiphase noble metal catalyst.
2. The preparation method according to claim 1, characterized in that: The modifier is selected from one or more combinations of octadecylamine (ODA), trimethylchlorosilane (TMS), and n-octadecyltrichlorosilane (OTS).
3. The preparation method according to claim 1, characterized in that: The concentration of the modifier solution is 0.01-0.2 g / mL, and the mass volume ratio of zeolite to the modified solution is 0.1-0.5 g / mL.
4. The preparation method according to claim 1, characterized in that: The zeolite includes one or more of Hγ zeolite, TS-1 zeolite, HZSM-5 zeolite, MCM-22 zeolite and mordenite.
5. The preparation method according to claim 1, characterized in that: The liquid phase chemical plating is carried out under stirring conditions, the stirring temperature is 20-50°C, and the stirring time is 2-4h.
6. The preparation method according to claim 1, characterized in that The precious metal of the precious metal salt solution includes one or more combinations of Pd, Pt, and Ir; and the loading amount of the precious metal in the bifunctional multiphase precious metal catalyst is 0.5 wt.%-3 wt.%.
7. The preparation method according to claim 1, characterized in that: The temperature of the reduction treatment is 350-550° C. and the time is 3-5 hours.
8. The bifunctional multiphase precious metal catalyst prepared by the preparation method according to any one of claims 1 to 7 is used in the low-temperature rapid release of hydrogen by slurry hydrogen storage and production materials, characterized in that: Under an inert atmosphere, the bifunctional multiphase precious metal catalyst is mixed with aluminum powder and subjected to ball milling to obtain an activated aluminum hydrolysis hydrogen production material; the activated aluminum hydrolysis hydrogen production material is then mixed with an organic liquid hydrogen storage material and subjected to ball milling to obtain an aluminum-based slurry hydrogen storage material.
9. The use according to claim 8, characterized in that: The organic liquid hydrogen storage material includes one or more combinations of fully hydrogenated N-propylcarbazole 12H-NPCZ, fully hydrogenated dibenzyltoluene 18H-DBT, fully hydrogenated 2-methylindole 8H-2-MID, and fully hydrogenated N-ethylcarbazole 12H-NECZ.
10. The use according to claim 9, characterized in that: In the aluminum-based slurry hydrogen storage material, the organic liquid hydrogen storage material, under the action of the activated aluminum hydrolysis hydrogen production material, has a hydrogen release conversion rate of 77.2%-87.8% when hydrolyzed for 20 minutes at an ambient temperature of 70-100°C.
Citation Information
Patent Citations
Method for preparing cis pinane by carrying out catalytic hydrogenation on alpha-pinene by amphiphilic molecular sieve loaded Ru nanoparticles
CN107188775A
Preparation method of cyclohexene hydration liquid-liquid amphiphilic catalyst
CN111450875A
Multi-medium composite slurry hydrogen storage and production material and preparation method thereof
CN118598072A
Catalyst for photocatalytic reaction for the production of hydrogen by hydrolysis and preparation method thereof
US20230264174A1
Generation of Hydrogen by Thermal Hydrolysis of Sodium Borohydrides
US20230271828A1